France : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This paper presents an overview of the different methodologies that can be used to measure the amount of available slack in an economy. A comparison of these alternatives reveals that the evolution of the Nairu is crucial for understanding recent cyclical developments in the French economy. A comprehensive reform of the personal income tax has been assessed. This paper analyzes the expansion of high-tech activities, and reviews a number of policy issues connected with the development of an information and communication technology-based new economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet